Factors contributing to SMEs failure in meeting supplier performance standards - Louise van Scheers (Foundations of Management, 2016)
This study sought to determine the factors that contribute to the failure of small and medium enterprises (SMEs) in meeting supplier performance standards. Suppliers are faced with the challenge of SMEs failing to meet supplier performance standards because they rely on these providers of products and services, mainly SMEs, for their operations and to ultimately achieve their mandate. The researchers were able to establish the main factors contributing to SME failure in meeting supplier performance standards. These are as follows: unclear specifications and terms of references from suppliers; insufficient information provided to SME suppliers to ensure understanding of requirements; insufficient feedback and support; no support of SME suppliers based on their Black Economic Empowerment (BEE) status; limited or no use of business support programs by SME suppliers; and external factors such as access to finance, changes in the economy, and location.
Keywords: 650; SME failure; supplier performance standards; BEE status